Menopausal hormone therapy in postmenopausal women: the quality of life today and in the long term - S V Yureneva; L M Ilyina; O V Yakushevskaya (IP Berlin A.V., 2016)
In considering the various aspects of menopause, not enough attention is paid to a significant reduction in the quality of life for women in transition and early postmenopause. Timely administration of menopausal hormone therapy is effective in reducing menopausal symptoms and improves quality of life at a given time, as well as the risk of developing diseases of aging, that can improve the quality of life related to health, and overall well-being of women in the more distant future. The choice of medication should be determined by its composition and clinical characteristics of the particular patient.